A comparison and analysis between current literature on the subjects of supplier selection and supply chain management with the actual working practice used at Nissan Technical Centre Europe. - Bourke, Kieran (2012)
As taken from the title, this paper aims to produce a comparison between the current literatures on the subject of supply chain management, with a specific focus on supplier selection, against that of actual working industry practice at Nissan Motor Co Limited. The paper discusses an introduction to the situation, defines relevant terms to be frequently used, and places the topic of supplier selection within the context of the supply chain as a whole. The paper then continues with the aforementioned literature review, and then proceeds to describe further the reasoning behind the collaboration with Nissan before revealing the approach taken by Nissan in their supply chain management and supplier selection process. The methodology used is explained. The findings are summarised, and from these a direct comparison with the literature is made. A conclusion is then drawn from the study.